2013
DOI: 10.1088/0964-1726/22/10/105001
|View full text |Cite
|
Sign up to set email alerts
|

Smart damping of laminated fuzzy fiber reinforced composite shells using 1–3 piezoelectric composites

Abstract: This paper deals with the investigation of active constrained layer damping (ACLD) of smart laminated continuous fuzzy fiber reinforced composite (FFRC) shells. The distinct constructional feature of a novel FFRC is that the uniformly spaced short carbon nanotubes (CNTs) are radially grown on the circumferential surfaces of the continuous carbon fiber reinforcements. The constraining layer of the ACLD treatment is considered to be made of vertically/obliquely reinforced 1–3 piezoelectric composite materials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Polymer nanocomposites embedded with nanoparticles such as CNTs, graphene and their derivatives, nanoclays, and silica nanoparticles have attracted a large amount of attention to achieve more improved thermomechanical properties than conventional composites . Among all others, CNTs have been emerged as the ideal candidates for multifarious applications due to their remarkable thermoelastic and physical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer nanocomposites embedded with nanoparticles such as CNTs, graphene and their derivatives, nanoclays, and silica nanoparticles have attracted a large amount of attention to achieve more improved thermomechanical properties than conventional composites . Among all others, CNTs have been emerged as the ideal candidates for multifarious applications due to their remarkable thermoelastic and physical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Attaching piezoelectric patches on passive system structures can make structural responses applicable for self-controlling and self-monitoring smart systems. Depending on their passive structures and piezoelectric designs, these smart systems can also offer other engineering applications such as damping vibrations [13], energy harvesting [4], fluid delivery [5,6] and damage detection [7]. However, due to the brittle behavior of piezoelectric materials, they should be attached to softer passive structures which can be one of the main objectives in the design of such smart structures.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that adding a small amount of CNTs in a polymeric matrix can considerably improve the mechanical properties of the resulted nanocomposite . Also, some research works have presented the successful use of piezoelectric fiber in the smart damping of CNTRC structures .…”
Section: Introductionmentioning
confidence: 99%